Comparative Analysis of Vaginal Birth After Cesarean (VBAC) Success Rates between Different Induction Methods - Dr. Dileepkumar Dattatray Rane; Dr. Viashali Atul Chaudhari; Dr. Jayashree Sunil Suryawanshi; Dr. Jayashree Sunil Suryawanshi; Dr. Sonal Chhagan Chaudhari; Dr. Bharti Anup Rathi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Vaginal Birth after Cesarean (VBAC) offers significant benefits over repeat cesarean sections, including reduced recovery times and lower complication rates. However, the success of VBAC largely depends on the method of labor induction used. This study evaluates the effectiveness and safety of different VBAC induction methods to ascertain optimal practices. Methods: This retrospective study analyzed 180 women who attempted VBAC at a tertiary care center from January 2015 to December 2019. The induction methods compared were mechanical (Foley catheter), pharmacological (Misoprostol), and Oxytocin. Outcomes measured included the success rate of VBAC, time to labor onset, maternal complications, and neonatal ICU admissions. Statistical analysis involved chi-square tests for categorical data, t-tests for continuous variables, and logistic regression to adjust for confounding factors. Results: The success rate of VBAC was highest with the mechanical method (62.96%), followed by Oxytocin (57.41%) and pharmacological methods (53.70%). The mechanical method also showed a statistically lower rate of maternal complications (14.81%) compared to the pharmacological (24.07%) and Oxytocin (18.52%) methods. Despite quicker labor onset with pharmacological induction, it did not translate to higher VBAC success. Conclusion: Mechanical induction methods such as the Foley catheter are associated with higher VBAC success rates and fewer maternal complications compared to pharmacological and Oxytocin inductions. These findings suggest that mechanical methods might offer a safer and more effective option for inducing labor in women attempting VBAC. However, individual patient factors must be considered when selecting the appropriate induction method.